Hybrid model predictive control framework for the thermal unit commitment problem including start-up and shutdown power trajectories - Foo, Eddy Yi Shyh (2018)
This paper presents a generalized mixed logical dynamical (MLD) approach for modelling thermal units. A self-scheduling problem is formulated for a thermal unit including an accurate model of its start-up and shutdown power trajectories. This optimal self-scheduling problem is solved in a Model Predictive Control (MPC) framework. The problem formulation considers all the relevant constraints associated with the scheduling of thermal units. The efficacy of the proposed MLD approach is demonstrated through simulation results. These results are extended to a system of 5 units and the optimal scheduling problem is formulated and solved.